Ripples of Trauma in Jonathan Safran Foer’s Extremely Loud & Incredibly Close and in Art Spiegelman’s In the Shadow of No Towers - Gwen Le Cor (Sillages Critiques)
This article examines how Jonathan Safran Foer (Extremely Loud & Incredibly Close) and Art Spiegelman (In the Shadow of No Towers) build on the traumatic choc wave spawned by 9/11. As traumatic repetitions spread through the text, they become a narrative device which both traces trauma and allows the reader to overcome its petrifying effect. The ripples of trauma thus weave together the fragmentary reiterations, allowing a narrative to emerge.